Corporate Farming for Farmer Labor Efficiency in Trimulyo Village, Bantul Regency - Neti Herlina; Ismiasih Ismiasih; Tri Endar Suswatiningsih (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
Agriculture is one of the dominant sectors in the economic structure in Daerah Istimewa Yogyakarta. This is because the agricultural sector contributes to meeting food needs and the supply of industrial raw materials. The corporate farming (CF) program located in desa Trimulyo, Daerah Istimewa Yogyakarta is one of the empowerment programs for farming communities by farming in groups. The purpose of this study was to determine the implementation of the CF program and the impact of the CF program on labor efficiency at the farm level. The research method used was descriptive qualitative and quantitative with t-test. The method of determining the sample was purposive with 30 farmers as respondents. The technique of collecting data was done by observation, interview and questionnaire. The results showed that the CF program is a program by combining several farmer-owned lands into one large area (land consolidation) and carried out jointly in one management from land preparation to harvest using modern agricultural tools and machines. The rice productivity produced by farmers before the CF program was 323.03 Kg/UT or 3,654.05 Kg/Ha. After the existence of the productivity program is 268.13 Kg/UT or 3,032 Kg/Ha. The need for labour in one season prior to the program was 43.8 HOK/UT or 1,464.76 HOK/Ha. The need for labor after the program was 31.52 HOK/UT or 716.79 HOK/Ha. The impact of the CF program on labor efficiency shows no significant difference. This means that the efficiency of the labor before and after the program is the same.